An aviator's field guide to middle-altitude flying : practical skills and tips for flying between 10,000 and 25,000 feet MSL - Blair, Jason (Aviation Supplies & Academics, Inc., 2018)
A flight instructor/examiner shares resources and discussion to help pilots transition or improve their skills flying piston-powered aircraft between 10,000-25,000 feet MSL.